IFPRI key facts series: Key facts sheet on poverty - Banda, Chimwemwe; Duchoslav, Jan (International Food Policy Research Institute, 2022)
This is the fourth in a series of Key Facts sheets that IFPRI is producing based on the Integrated Household Surveys (IHS). The purpose of the series is to present data relevant to key policy issues on agriculture, food systems, and development topics in Malawi. Other Key Facts Sheets are available on our website at massp.ifpri.info.